Talent detection—importance of the will and the ability when starting a sport activity - Spies, F.; Schauer, L.; Bindel, T.; Pfeiffer, M. (German Journal of Exercise and Sport Research, 2022)
The early identification of sports talents includes finding the right sport and is of great importance for both scientists and practitioners. In this article, special attention will be paid to the entry into sports in general as a basis of a talent development process. Sport-specific evidence from a variety of talent development models will be listed and research gaps will be identified. For this purpose, this article refers to a model that can be classified as both process and structure oriented and tries to find domain-specific application. A framework is presented as a research approach in which the different scientific disciplines can bring together their subject areas. This enables so-called ability-personality profiles consisting individual constellations of motivation variables, interests, skills, and experience to be studied together and incorporated into the talent development process. The arrangement of movement offers should be oriented to the individual profiles. At the same time, movement experiences can offer the basis for the formation of interests, motivation, and sport-motor skills, i.e., of the will and the ability. Taking the will into account as well as the ability could lead people to detect their own talent (based on contents of the presented framework) and the sport that is suitable for them, and thus be ready for the entry to the path of talent development.